Lithium supplement agent and preparation method and application thereof

By using lithium-ion batteries with core-shell structures, the core is lithium ferrate or lithium silicate, and the outer shell is lithium-rich lithium nickelate and other materials, the problem of gas production of Li5FeO4 lithium-supplement agent is solved, and the battery is improved Cycle performance and safety.

CN119447263APending Publication Date: 2025-02-14BATTEROTECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411682992.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Among existing lithium-ion batteries, Li5FeO4 has gas production problems when used as a lithium supplement agent, which affects the battery's circulation performance and safety.

Method used

Lithium supplement agents that use core-shell structures, the core material is lithium ferrate or lithium silicate, and the outer shell material is lithium-rich lithium nickelate, nickel-cobalt manganese ternary material or nickel-cobalt binary material, which reduces gas production through the cladding layer.

Benefits of technology

The battery charge and discharge specific capacity and cycle retention rate are improved, the gas production is reduced, and the battery stability and safety is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447263A_ABST
    Figure CN119447263A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium supplement agent and a preparation method and application thereof, and belongs to the technical field of lithium supplement agents. The lithium supplement agent comprises a core-shell structure, a material forming an inner core comprises at least one of a lithium ferrite material and a lithium silicate material, and a material forming a shell comprises at least one of lithium-rich lithium nickelate, a nickel-cobalt-manganese ternary material and a nickel-cobalt binary material; and at least part of the material forming the shell coats the surface of the inner core. The shell material can have part of Ni < 3 + > and / or Ni < 4 + > ions in a reaction system, and in the circulation and storage process after the battery cell is prepared, the shell material reacts with oxygen released by a very small amount of the core material which is not completely decomposed and various oxygen ions dissolved in the electrolyte, so that the ring-opening reaction of ethylene carbonate in the electrolyte is reduced, and the gas production is reduced. The preparation method comprises the step of preparing the shell on the surface of the core. The method is simple, easy to operate and suitable for industrial production. The lithium supplement agent can be used for preparing a battery, especially a battery with a graphite system as a negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium supplement agents, and in particular to a lithium supplement agent and a preparation method and application thereof. Background Art

[0002] The commonly used positive electrode lithium supplement is to add lithium-rich metal oxides, such as Li5FeO4 (hereinafter referred to as LFO) and other materials, during the preparation of the positive electrode material to compensate for the efficiency loss of the negative electrode during the first charge and discharge. The mechanism of adding Li5FeO4 is as follows: during the first charge, the lithium supplement will release a specific capacity of >700mAh / g, while the first discharge capacity is generally 30mAh / g to 40mAh / g. It produces excess lithium ions to supplement the lithium loss of the graphite negative electrode and release oxygen.

[0003] The first charge and discharge mechanism of Li5FeO4 mentioned above is as follows:

[0004] Li5FeO4→Li3FeO 3.5 +0.25O2(Gas)+2Li + +2e - ;

[0005] Li3FeO 3.5 →LiFeO2+0.75O2(Gas)+2Li + +2e - .

[0006] The initial charging capacity of Li5FeO4 is above 700mAh / g, which can effectively supplement the lithium ion consumption of the negative electrode SEI film during the first week of formation of lithium-ion batteries (especially LFP / Gr systems), thereby improving the battery capacity and cycle performance. During the charging process of Li5FeO4, there are two charging platforms, the first platform is around 3.5V, and the second platform is around 3.9V. The two charging platforms correspond to these two different charging stages. At around 3.5V, Li5FeO4 will release 2 Li, accompanied by the generation of 0.25O2, and at around 3.9V, there will be 0.75O2 released. That is, although Li5FeO4 will supplement the lithium ion consumption of the SEI film during the first charging process, its own gas production problem will bring new challenges to the battery.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The purpose of the present invention is to provide a lithium supplement and a preparation method and application thereof, so as to solve or improve the above technical problems.

[0009] The present invention can be implemented like this:

[0010] In a first aspect, the present invention provides a lithium supplement, the lithium supplement comprising a core-shell structure, wherein the material forming the inner core comprises at least one of a lithium ferrite material and a lithium silicate material, and the material forming the outer shell comprises at least one of a lithium-rich nickel oxide, a nickel-cobalt-manganese ternary material, and a nickel-cobalt binary material;

[0011] At least a portion of the material forming the outer shell covers the surface of the inner core.

[0012] In an optional embodiment, the lithium supplement comprises a lithium ferrite material and a lithium-rich nickel oxide material;

[0013] The lithium ferrite material forms the inner core, and at least a portion of the lithium-rich nickel-based lithium oxide material is coated on the surface of the lithium ferrite material.

[0014] In an optional embodiment, the shell of the lithium supplement includes a lithium-rich lithium nickelate coating layer coated on the surface of the lithium ferrite material, and a lithium-rich lithium nickelate material free on the surface of the lithium-rich lithium nickelate coating layer or existing alone.

[0015] In an optional embodiment, the surface of the lithium ferrite material has a carbon coating layer, and the lithium-rich lithium nickel oxide coating layer is located on the surface of the carbon coating layer;

[0016] In an optional embodiment, the thickness of the lithium-rich lithium nickelate coating layer is 100 nm to 3 μm.

[0017] In a second aspect, the present invention provides a method for preparing a lithium supplement as described in the aforementioned embodiment, comprising the following steps: preparing a core, and preparing a shell on the surface of the core.

[0018] In an optional embodiment, the lithium supplement comprises a lithium ferrite material and a lithium-rich nickel oxide material;

[0019] The mixture including the first lithium source and the iron source is pre-sintered first, and then sintered for the first time to obtain a lithium ferrite material; the lithium ferrite material is mixed with the second lithium source and the nickel source and then sintered for the second time to obtain a lithium ferrite material with a lithium-rich nickel oxide coating layer.

[0020] In an optional embodiment, the mixture includes at least one of the following characteristics:

[0021] Feature 1: The molar ratio of Li in the first lithium source to Fe in the iron source is 1.01:1 to 1.50:1;

[0022] Feature 2: The first lithium source includes at least one of lithium hydroxide, lithium oxide, lithium carbonate and lithium acetate; preferably, the first lithium source includes at least one of lithium oxide and lithium hydroxide;

[0023] Feature 3: D of the first lithium source 50 10μm~30μm;

[0024] Feature 4: The iron source includes at least one of Fe2O3, FeCl3 and Fe(NO3)3; preferably, the iron source includes Fe2O3;

[0025] Feature 5: The mixture also includes a carbon source; preferably, the carbon source includes an organic carbon source; more preferably, the carbon source includes at least one of glucose and acetylene black; preferably, the amount of carbon source added is 0.5% to 5% of the total mass of the lithium ferrite material.

[0026] In an optional embodiment, the pre-sintering temperature is 400° C. to 500° C., and the pre-sintering time is 7 h to 10 h.

[0027] In an alternative embodiment, pre-sintering is performed under an inert atmosphere.

[0028] In an optional embodiment, the temperature of the first sintering is 600° C. to 900° C.; the time of the first sintering is 5 h to 15 h.

[0029] In an alternative embodiment, the first sintering is performed in an inert atmosphere.

[0030] In an optional embodiment, the heating rate of the first sintering is 1° C. / min to 10° C. / min.

[0031] In an optional embodiment, the molar ratio of Li in the second lithium source to Ni in the nickel source is 1.1:1 to 1.5:1, and the mass ratio of the nickel source to the lithium ferrite material is 0.01:1 to 5:1.

[0032] In an alternative embodiment, the second lithium source includes at least one of lithium hydroxide, lithium oxide, lithium carbonate and lithium acetate.

[0033] In an alternative embodiment, the nickel source includes at least one of Ni(OH)2, NiO and NiCO3.

[0034] In an optional embodiment, the temperature of the second sintering is 500° C. to 800° C.; and the time of the second sintering is 6 h to 15 h.

[0035] In an alternative embodiment, the second sintering is performed in an inert atmosphere.

[0036] In an optional embodiment, the heating rate of the second sintering is 1° C. / min to 10° C. / min.

[0037] In an optional embodiment, the lithium ferrite material is first crushed for the first time to obtain a first crushed material; the first crushed material is then mixed with a second lithium source and a nickel source and then sintered for a second time.

[0038] In an optional embodiment, the particle size of the first crushed material ranges from 0.5 μm to 10 μm.

[0039] In an optional embodiment, the second sintered material obtained by the second sintering is crushed for the second time.

[0040] In an optional embodiment, the particle size of the material after the second crushing is in the range of 5 μm to 15 μm.

[0041] In a third aspect, the present invention provides a use of the lithium supplement agent according to the aforementioned embodiment in battery preparation.

[0042] In an optional embodiment, the lithium supplement is used in the preparation of the positive electrode plate in the battery.

[0043] In an optional embodiment, the lithium supplement agent is used to prepare the positive electrode slurry for the positive electrode sheet.

[0044] In an optional embodiment, the positive electrode slurry includes a lithium iron phosphate positive electrode material, a conductive agent, a binder, and a lithium supplement agent.

[0045] In an optional embodiment, the positive electrode slurry includes 0.5 wt% to 5 wt% of a lithium supplement, 92 wt% to 98 wt% of a lithium iron phosphate positive electrode material, 0.5 wt% to 3 wt% of a conductive agent, and the remainder is a binder.

[0046] In an optional embodiment, the negative electrode material of the battery is a graphite system material.

[0047] The beneficial effects of the present invention include:

[0048] The lithium supplement provided by the present invention has a core-shell structure. By using specific materials as the core and the shell, the stability of the core material in the air can be increased by mutual cooperation. In addition, the setting of the shell is conducive to increasing the contact area between the core material and the shell material, providing favorable conditions for the shell material to act on the core material. In addition, the shell material will have some Ni in the reaction system. 3+ and / or Ni 4+ During the circulation and storage process after the battery cell is manufactured, these nickel ions can react with the oxygen released by the very small amount of core material that has not been completely decomposed and the various oxygen ions dissolved in the electrolyte under the action of electrochemistry to generate substances such as NiO and / or NiO2, which is beneficial to reduce the ring-opening reaction of ethylene carbonate in the electrolyte and further reduce gas production.

[0049] In addition, the preparation method of the lithium supplement is simple, easy to operate, and can be industrially produced. The lithium supplement can be used to prepare batteries, especially for preparing batteries whose negative electrode materials are graphite system materials, to improve the charge and discharge specific capacity and cycle retention rate of the battery, and to reduce gas production. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0051] Figure 1 This is a schematic diagram of the structure of the lithium supplement provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0052] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0053] The lithium supplement agent provided by the present invention and its preparation method and application are described in detail below.

[0054] The present invention provides a lithium supplement agent, which includes a core-shell structure, wherein the material forming the core includes at least one of a lithium ferrite material and a lithium silicate material, and the material forming the shell includes at least one of lithium-rich nickel oxide (Li2NiO2, referred to as LNO), a nickel-cobalt-manganese ternary material, and a nickel-cobalt binary material;

[0055] At least a portion of the material forming the outer shell covers the surface of the inner core.

[0056] In some embodiments, part of the material forming the shell is coated on the surface of the core to form an outer coating layer, and part of the material forming the shell is free on the surface of the outer coating layer or exists alone.

[0057] In some embodiments, the lithium supplement includes a lithium ferrite material and a lithium-rich nickel oxide material. The lithium ferrite material forms a core, and at least a portion of the lithium-rich nickel oxide material is coated on the surface of the lithium ferrite material.

[0058] Exemplarily, the shell of the lithium supplement includes a lithium-rich lithium nickelate coating layer coated on the surface of the lithium ferrite material, and a lithium-rich lithium nickelate material that is free on the surface of the lithium-rich lithium nickelate coating layer or exists alone.

[0059] In other words, the above-mentioned lithium-rich nickel acid coating layer can be continuous or discontinuous. When the lithium-rich nickel acid coating layer is continuous, it can only have a coating structure continuously formed by the lithium-rich nickel acid material; in addition, it can also contain a part of the lithium-rich nickel acid material in the form of particles while forming a continuous coating structure formed by part of the lithium-rich nickel acid material. When the lithium-rich nickel acid coating layer is discontinuous, the lithium-rich nickel acid material coats the core structure in the form of particles, that is, there are gaps between at least some of the lithium-rich nickel acid particles.

[0060] In some embodiments, the surface of the lithium ferrite material further has a carbon coating layer, and the lithium-rich lithium nickel oxide coating layer is located on the surface of the carbon coating layer.

[0061] For example, the thickness of the lithium-rich nickelate coating layer may be 100 nm to 3 μm.

[0062] In some other embodiments, the lithium ferrite material may be completely or partially replaced by a lithium silicate material.

[0063] The above-mentioned lithium-rich nickel oxide material will have some Ni in the reaction system. 3+ and / or Ni 4+ During the circulation and storage process after the battery cell is manufactured, these nickel ions can react with the oxygen released by the very small amount of core material that has not been completely decomposed and the various oxygen ions dissolved in the electrolyte under the action of electrochemistry to generate substances such as NiO and / or NiO2, which is beneficial to reduce the ring-opening reaction of ethylene carbonate in the electrolyte and further reduce gas production.

[0064] As mentioned above, the lithium supplement provided by the present invention can enable the corresponding battery to have a higher specific capacity and cycle retention rate, and produce less gas.

[0065] Correspondingly, the present invention also provides a method for preparing the above-mentioned lithium supplement, comprising the following steps: preparing a core, and preparing a shell on the surface of the core.

[0066] In some embodiments, taking the lithium supplement agent including a lithium ferrite material and a lithium-rich lithium nickel oxide material as an example, the preparation method of the lithium supplement agent includes: pre-sintering a mixture including a first lithium source and an iron source, and then performing a first sintering to obtain a lithium ferrite material; mixing the lithium ferrite material with a second lithium source and a nickel source and performing a second sintering to obtain a lithium ferrite material having a lithium-rich lithium nickel oxide coating layer.

[0067] Among them, the molar ratio of Li in the first lithium source to Fe in the iron source is 1.01:1 to 1.50:1, such as 1.01:1, 1.05:1, 1.10:1, 1.15:1, 1.20:1, 1.25:1, 1.30:1, 1.35:1, 1.40:1, 1.45:1 or 1.50:1, or other values ​​within the range of 1.01:1 to 1.50:1.

[0068] The first lithium source may illustratively but not limitatively include at least one of lithium hydroxide, lithium oxide, lithium carbonate and lithium acetate. In some optional embodiments, the first lithium source includes at least one of lithium oxide and lithium hydroxide.

[0069] D of the first lithium source 50 It can be 10 μm to 30 μm, such as 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, or any other value within the range of 10 μm to 30 μm.

[0070] The iron source illustratively but not limitedly includes at least one of Fe2O3, FeCl3 and Fe(NO3)3. In some optional embodiments, the iron source includes Fe2O3.

[0071] In some embodiments, the mixture further includes a carbon source. The carbon source may include an organic carbon source, such as at least one of glucose and acetylene black. The amount of the carbon source added may be 0.5% to 5% of the total mass of the lithium ferrite material, such as 0.5%, 1%, 2%, 4% or 5%, etc., or may be other values ​​within the range of 0.5% to 5%.

[0072] In the present invention, the pre-sintering temperature may be 400°C to 500°C, such as 400°C, 420°C, 450°C, 480°C or 500°C, or any other value within the range of 400°C to 500°C.

[0073] The pre-sintering time may be 7 h to 10 h, such as 7 h, 8 h, 9 h or 10 h, or any other value within the range of 7 h to 10 h.

[0074] The pre-sintering is performed in an inert atmosphere, which may exemplarily but not limitedly include at least one of a nitrogen atmosphere and an argon atmosphere, the same below.

[0075] The present invention pre-sinters the mixed material before the first sintering, which is beneficial to obtaining a lithium ferrite material with better structure and more stable performance.

[0076] If the pre-sintering temperature is lower than 400°C, it is easy to cause insufficient sintering of the material and lattice defects; if the pre-sintering temperature is higher than 500°C, it is easy to cause the sintering time process and the reaction time is too long, resulting in material performance defects. The pre-sintering time can be 7h to 10h, such as 7h, 8h, 9h or 10h, etc., or other values ​​within the range of 7h to 10h.

[0077] In some optional embodiments, the temperature of the first sintering may be 600°C to 900°C, such as 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, or other values ​​within the range of 600°C to 900°C.

[0078] The first sintering time may be 5 h to 15 h, such as 5 h, 8 h, 10 h, 12 h or 15 h, etc., or may be other values ​​within the range of 5 h to 15 h.

[0079] The heating rate of the first sintering can be 1°C / min to 10°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, or other values ​​within the range of 1°C / min to 10°C / min.

[0080] The first sintering is carried out in an inert atmosphere.

[0081] By sintering the mixture for the first time under the above conditions, a lithium ferrite material can be generated. When the mixture contains a carbon source, the surface of the lithium ferrite material also has a carbon coating layer, which is beneficial to improving the conductivity and structural stability of the lithium ferrite material.

[0082] Furthermore, the lithium ferrite material can be crushed for the first time to obtain a first crushed material; and then the first crushed material is mixed with a second lithium source and a nickel source and then sintered for the second time.

[0083] The particle size of the first crushed material may range from 0.5 μm to 10 μm, such as 0.5 μm, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm or 10 μm, or may be other values ​​within the range of 0.5 μm to 10 μm.

[0084] In some optional embodiments, the molar ratio of Li in the second lithium source to Ni in the nickel source can be 1.1:1 to 1.5:1, such as 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, or other values ​​within the range of 1.1:1 to 1.5:1.

[0085] The mass ratio of the nickel source to the lithium ferrite material can be 0.01:1 to 5:1, such as 0.01:1, 0.05:1, 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1 or 5:1, or other values ​​within the range of 0.01:1 to 5:1.

[0086] The second lithium source may illustratively but not limitatively include at least one of lithium hydroxide, lithium oxide, lithium carbonate and lithium acetate.

[0087] The nickel source may illustratively but not limitatively include at least one of Ni(OH)2, NiO and NiCO3.

[0088] In some optional embodiments, the temperature of the second sintering may be 500°C to 800°C, such as 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, or other values ​​within the range of 500°C to 800°C.

[0089] The second sintering time may be 6 h to 15 h, such as 6 h, 8 h, 10 h, 12 h or 15 h, etc., or may be other values ​​within the range of 6 h to 15 h.

[0090] The heating rate of the second sintering can be 1°C / min to 10°C / min, such as 1°C / min, 2°C / min, 5°C / min, 8°C / min or 10°C / min, or other values ​​within the range of 1°C / min to 10°C / min.

[0091] The second sintering is carried out in an inert atmosphere.

[0092] Furthermore, the second sintered material obtained by the second sintering can be crushed for the second time. The particle size of the material after the second crushing can range from 5 μm to 15 μm.

[0093] The material after the second crushing can also be screened as needed.

[0094] In the above-mentioned first sintering process, the surface energy provided by the first lithium source in the molten state can fully fuse and sinter the primary lithium ferrite grains, reduce the grain size of the lithium ferrite, and reduce the subsequent lattice fission of the material that leads to electrolyte erosion. The lithium-rich nickel oxide material generated by the second sintering will have some Ni in the reaction system. 3+ and / or Ni 4+During the circulation and storage process after the battery cell is manufactured, these nickel ions can react with the oxygen released by the very small amount of core material that has not been completely decomposed and the various oxygen ions dissolved in the electrolyte under the action of electrochemistry to generate substances such as NiO and / or NiO2, which is beneficial to reduce the ring-opening reaction of ethylene carbonate in the electrolyte and further reduce gas production.

[0095] In some other embodiments, taking the lithium supplement agent including lithium silicate material and lithium-rich nickel oxide material as an example, the preparation method of the lithium supplement agent is substantially the same as the preparation method using lithium ferrite material as the core material.

[0096] In some other embodiments, taking the lithium supplement agent including lithium ferrite material and nickel-cobalt-manganese ternary material (wherein the molar ratio of Ni, Co and Mn can be 8:1:1, 6:2:2 or 5:2:3, etc.) as an example, the preparation method of the lithium supplement agent is generally the same as the preparation method using lithium-rich nickel oxide as the shell material.

[0097] In some other embodiments, taking the lithium supplement agent including lithium ferrite material and nickel-cobalt binary material as an example, the preparation method of the lithium supplement agent is substantially the same as the preparation method using lithium-rich nickel oxide as the shell material.

[0098] In addition, the present invention also provides an application of the lithium supplement agent in battery preparation.

[0099] In some optional ways, the lithium supplement is used to prepare the positive electrode plate in the battery. Exemplarily, the battery can be a lithium iron phosphate (abbreviated as "LFP") battery, and the negative electrode material in the negative electrode contained therein can be a graphite system material.

[0100] Specifically, the lithium supplement agent can be used to prepare positive electrode slurry for positive electrode plates. The positive electrode slurry may include lithium iron phosphate positive electrode material, a conductive agent, a binder and a lithium supplement agent.

[0101] Among them, the positive electrode slurry may include 0.5wt% to 5wt% (such as 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc.) of a lithium supplement, 92wt% to 98wt% (such as 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt% or 98wt%, etc.) of a lithium iron phosphate positive electrode material, 0.5wt% to 3wt% (such as 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%, etc.) of a conductive agent, and the remainder is a binder.

[0102] Exemplarily, the binder may include at least one of polyvinylidene fluoride, polyvinylidene fluoride, styrene butadiene rubber, and polyvinyl alcohol. The conductive agent may include at least one of carbon nanotubes, Super-P, and graphene.

[0103] The remaining conditions and methods for preparing the battery can be referred to the relevant prior art and will not be elaborated here.

[0104] By using the lithium supplement provided by the present invention in a battery in which a lithium iron phosphate positive electrode material and a graphite system negative electrode material are combined, the DC internal resistance of the battery can be effectively reduced and the electrochemical performance of the battery can be improved.

[0105] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0106] Example 1

[0107] This embodiment provides a lithium supplement, and the preparation method thereof comprises:

[0108] S1: preparing a mixture.

[0109] The first lithium source, the iron source and the carbon source were mixed in a ball mill (rotation speed of 8000 rpm) for 12 hours to obtain a mixture. 50 The first lithium source is 20 μm lithium hydroxide, the iron source is Fe2O3, and the carbon source is glucose. The molar ratio of Li in the first lithium source to Fe in the iron source is 1.05:1, and the amount of the carbon source added is 2.5 wt% of the total mass of the lithium ferrite material.

[0110] S2: First sintering.

[0111] The mixed material obtained in S1 is pre-sintered in an argon atmosphere at a temperature of 450°C for 8 hours. The mixed material is then heated to 800°C at a heating rate of 5°C / min for a first sintering for 10 hours to obtain a lithium ferrite material. The lithium ferrite material is crushed for the first time to obtain a first crushed material with a particle size range of 0.5 μm to 10 μm.

[0112] S3: Second mixing.

[0113] The second lithium source, the nickel source and the first crushed material obtained by S2 were mixed in a high-speed mixer (rotation speed of 6000 rpm) for 10 hours. The second lithium source was lithium hydroxide, the nickel source was Ni(OH)2, the molar ratio of Li in the second lithium source to Ni in the nickel source was 1.2:1, and the mass ratio of the nickel source to the lithium ferrite material was 2:1.

[0114] S4: Second sintering.

[0115] The mixed material obtained in S3 is sintered for the second time in an argon atmosphere. The temperature of the second sintering is 650°C, the time of the second sintering is 10 hours, and the heating rate is 5°C / min to obtain a second sintered material. The second sintered material is crushed for the second time to obtain a second crushed material with a particle size range of about 9 μm. The second crushed material is sieved to obtain a lithium supplement with an average particle size of 8 μm to 10 μm.

[0116] Example 2

[0117] The difference between this embodiment and embodiment 1 is that the temperature of the first sintering is 700°C.

[0118] Example 3

[0119] The difference between this embodiment and embodiment 1 is that the temperature of the first sintering is 900°C.

[0120] Example 4

[0121] The difference between this embodiment and embodiment 1 is that the molar ratio of Li in the first lithium source to Fe in the iron source is 1.02:1.

[0122] Example 5

[0123] The difference between this embodiment and embodiment 1 is that the molar ratio of Li in the first lithium source to Fe in the iron source is 1.1:1.

[0124] Example 6

[0125] The difference between this embodiment and embodiment 1 is that the molar ratio of Li in the first lithium source to Fe in the iron source is 1.15:1.

[0126] Example 7

[0127] The difference between this embodiment and embodiment 1 is that the mass ratio of the nickel source to the lithium ferrite material is 3:1.

[0128] Example 8

[0129] The difference between this embodiment and embodiment 1 is that the mass ratio of the nickel source to the lithium ferrite material is 4:1.

[0130] Example 9

[0131] The difference between this embodiment and embodiment 1 is that the mixed material of S1 does not contain a carbon source.

[0132] Example 10

[0133] This embodiment provides a lithium supplement, and the preparation method thereof comprises:

[0134] S1: preparing a mixture.

[0135] The first lithium source, the iron source and the carbon source were mixed in a ball mill (rotation speed of 8000 rpm) for 12 hours to obtain a mixture. 50 The first lithium source is 10 μm lithium oxide, the iron source is FeCl3, and the carbon source is acetylene black. The molar ratio of Li in the first lithium source to Fe in the iron source is 1.01:1, and the amount of the carbon source added is 0.5wt% of the total mass of the lithium ferrite material.

[0136] S2: First sintering.

[0137] The mixed material obtained in S1 was pre-sintered in a nitrogen atmosphere at a temperature of 400°C for 10 hours. Then, the mixture was heated to 600°C at a heating rate of 1°C / min for a first sintering for 8 hours to obtain a lithium ferrite material. The lithium ferrite material was crushed for a first time to obtain a first crushed material with a particle size range of 0.5 μm to 10 μm.

[0138] S3: Second mixing.

[0139] The second lithium source, the nickel source and the first crushed material obtained in S2 were mixed in a high-speed mixer (rotation speed of 6000 rpm) for 10 hours. The second lithium source was lithium oxide, the nickel source was NiO, the molar ratio of Li in the second lithium source to Ni in the nickel source was 1.1:1, and the mass ratio of the nickel source to the lithium ferrite material was 0.01:1.

[0140] S4: Second sintering.

[0141] The mixed material obtained in S3 is sintered for the second time in a nitrogen atmosphere. The temperature of the second sintering is 500°C, the time of the second sintering is 6 hours, and the heating rate is 1°C / min to obtain a second sintered material. The second sintered material is crushed for the second time to obtain a second crushed material with a particle size range of 9 μm, and the second crushed material is sieved to obtain a lithium supplement with an average particle size of 8 μm to 10 μm.

[0142] Embodiment 11

[0143] This embodiment provides a lithium supplement, and the preparation method thereof comprises:

[0144] S1: preparing a mixture.

[0145] The first lithium source, the iron source and the carbon source were mixed in a ball mill (rotation speed of 8000 rpm) for 12 hours to obtain a mixture. 50 The first lithium source is 30 μm lithium carbonate, the iron source is Fe(NO3)3, and the carbon source is glucose. The molar ratio of Li in the first lithium source to Fe in the iron source is 1.50:1, and the amount of carbon source added is 5wt% of the total mass of the lithium ferrite material.

[0146] S2: First sintering.

[0147] The mixed material obtained in S1 is pre-sintered in an argon atmosphere at a temperature of 500°C for 7 hours. Then, the mixture is heated to 900°C at a heating rate of 10°C / min for a first sintering, and the first sintering time is 10 hours to obtain a lithium ferrite material; the lithium ferrite material is crushed for the first time to obtain a first crushed material with a particle size range of 0.5μm to 10μm.

[0148] S3: Second mixing.

[0149] The second lithium source, the nickel source and the first crushed material obtained by S2 were mixed in a high-speed mixer (rotation speed of 6000 rpm) for 10 hours. The second lithium source was lithium carbonate, the nickel source was NiCO3, the molar ratio of Li in the second lithium source to Ni in the nickel source was 1.5:1, and the mass ratio of the nickel source to the lithium ferrite material was 5:1.

[0150] S4: Second sintering.

[0151] The mixed material obtained in S3 is sintered for the second time in an argon atmosphere. The temperature of the second sintering is 800°C, the time of the second sintering is 15h, and the heating rate is 10°C / min to obtain a second sintered material. The second sintered material is crushed for the second time to obtain a second crushed material with a particle size range of 9μm, and the second crushed material is sieved to obtain a lithium supplement with an average particle size of 8μm to 10μm.

[0152] Example 12

[0153] This embodiment provides a lithium supplement agent, the core of which is lithium silicate and the shell of which is lithium-rich nickelate. The preparation method of the lithium supplement agent includes:

[0154] S1: preparing a mixture.

[0155] D 50 Lithium carbonate with a particle size of 30 μm and SiO2 were added to a ball mill (rotation speed of 8000 rpm) and mixed for 12 hours to obtain a mixture. The molar ratio of Li in lithium carbonate to Si in SiO2 was 1.50:1.

[0156] S2: First sintering.

[0157] The mixed material obtained in S1 was pre-sintered in an argon atmosphere at a temperature of 500°C for 7 hours. Then, the mixture was heated to 700°C at a heating rate of 10°C / min for a first sintering, and the first sintering time was 12 hours to obtain Li4SiO4 material. The Li4SiO4 material was crushed for the first time to obtain a first crushed material with a particle size range of 1μm to 10μm.

[0158] S3 and S4 are the same as in Example 1.

[0159] Embodiment 13

[0160] This embodiment provides a lithium supplement agent, the core of which is lithium ferrite and the shell of which is a nickel-cobalt-manganese ternary material. The preparation method of the lithium supplement agent includes:

[0161] S1 and S2 are the same as in Example 1.

[0162] S3: Second mixing.

[0163] The second lithium source, the nickel source and the first crushed material obtained from S2 were mixed in a high-speed mixer (rotation speed of 800 rpm) for 5 h. 50 The nanostructured lithium ion battery is 30 μm LiOH, the nickel source is a NiCoMn precursor (taking NCM811 as an example), the molar ratio of Li in the second lithium source to Ni in the nickel source is 1.5:1, and the mass ratio of the nickel source to the lithium ferrite material is 5:1.

[0164] S4: Second sintering.

[0165] The mixed material obtained in S3 is subjected to a second sintering in an oxygen atmosphere, the second sintering temperature is 700°C, the second sintering time is 12 hours, and the heating rate is 10°C / min to obtain a second sintered material. The second sintered material is subjected to a second crushing to obtain a second crushed material with a particle size range of about 9 μm, and the second crushed material is sieved to obtain a lithium supplement with an average particle size of 8 μm to 10 μm.

[0166] Embodiment 14

[0167] This embodiment provides a lithium supplement agent, the core of which is lithium ferrite and the shell of which is a nickel-cobalt binary material. The preparation method of the lithium supplement agent includes:

[0168] S1 and S2 are the same as in Example 1.

[0169] S3: Second mixing.

[0170] The second lithium source, the nickel source and the first crushed material obtained from S2 were mixed in a high-speed mixer (rotation speed of 800 rpm) for 5 h. 50 The lithium ion battery is 30 μm LiOH, the nickel source is a NiCo precursor (taking NiCo64 as an example), the molar ratio of Li in the second lithium source to Ni in the nickel source is 1.5:1, and the mass ratio of the nickel source to the lithium ferrite material is 5:1.

[0171] S4: Second sintering.

[0172] The mixed material obtained in S3 is subjected to a second sintering in an oxygen atmosphere, the second sintering temperature is 800°C, the second sintering time is 12h, and the heating rate is 10°C / min to obtain NC64 second sintering material. The second sintering material is subjected to a second crushing to obtain a second crushing material with a particle size range of about 9μm, and the second crushing material is sieved to obtain a lithium supplement with an average particle size of 8μm to 10μm.

[0173] Comparative Example 1

[0174] The difference between this comparative example and Example 2 is that no pre-sintering treatment is performed during the preparation of the inner core, and no subsequent outer shell preparation is performed.

[0175] Comparative Example 2

[0176] The difference between this comparative example and Example 2 is that no pre-sintering treatment is performed during the preparation of the inner core.

[0177] Comparative Example 3

[0178] The difference between this comparative example and Example 2 is that the pre-sintering temperature is 350°C.

[0179] Comparative Example 4

[0180] The difference between this comparative example and Example 2 is that the pre-sintering temperature is 550°C.

[0181] Comparative Example 5

[0182] The difference between this comparative example and Example 2 is that the pre-sintering time is 5 hours.

[0183] Comparative Example 6

[0184] The difference between this comparative example and Example 2 is that the pre-sintering time is 10 hours.

[0185] Test example

[0186] ①, taking the lithium supplement prepared in Example 1 as an example, Figure 1 As shown, the lithium supplement includes a lithium-rich nickelate material and a lithium ferrite material with a carbon coating layer, part of the lithium-rich nickelate material forms a continuous lithium-rich nickelate coating layer on the surface of the carbon coating layer, and part of the lithium-rich nickelate material exists in the lithium supplement in the form of particles. The thickness of the carbon coating layer is about 500nm, and the thickness of the lithium-rich nickelate coating layer is 2μm.

[0187] ②. The lithium supplement prepared in Examples 1 to 14 and Comparative Examples 1 to 6 were added to the positive electrode slurry in the following manner and further prepared into a battery.

[0188] Preparation of positive electrode slurry: Mix lithium iron phosphate positive electrode material, conductive agent (Super P), binder (PVDF) and lithium supplement agent in a ratio of 95:2:0.5:2.5.

[0189] The negative electrode adopts a graphite system, and the specific preparation method of the negative electrode slurry is as follows: the graphite negative electrode material, the conductive agent (Super P), the binder (PVDF), and the dispersant (CMC) are mixed according to 96.6:0.5:1.8:1.1.

[0190] Subsequently, the positive electrode slurry and the negative electrode slurry are coated on the positive electrode collector (aluminum foil) and the negative electrode collector (copper foil) respectively, and then the battery is prepared according to the steps of rolling, slitting, lamination, assembly, liquid injection, sealing and formation.

[0191] A. The charging specific capacity test was performed on the batteries obtained in Examples 1 to 14 and Comparative Examples 1 to 6. The test conditions were as follows: charging at a constant current of 0.1C to 4.3V, constant voltage to 0.02C, and discharging at a constant current of 0.1C to 2.0V. The results are shown in Tables 1 and 2.

[0192] Table 1 Test results

[0193]

[0194]

[0195] Table 2 Test results

[0196]

[0197] B. The batteries obtained in Examples 1 to 14 and Comparative Examples 1 to 6 were tested for full battery discharge specific capacity, capacity retention after 45 cycles, and gas production. The results are shown in Table 3.

[0198] Among them, the full battery discharge specific capacity and the capacity retention rate after 45 cycles are carried out according to the conditions in A, and the gas production test method is the water displacement method to measure the volume. "D" stands for "day".

[0199] Table 3 Test results

[0200] Serial number Full battery discharge capacity (mAh / g) 45℃ cycle retention rate (%) Gas production Comparative Example 1 142.78 1000 weeks 87.43% 35D@12.04% Comparative Example 2 143.35 1000 weeks 89.67% 35D@10.67% Comparative Example 3 143.98 1000 weeks 88.65% 35D@11.39% Comparative Example 4 144.65 1000 weeks 89.01% 35D@10.87% Comparative Example 5 144.27 1000 weeks 87.96% 35D@12.87% Comparative Example 6 144.26 1000 weeks 88.36% 35D@10.98% Example 1 146.75 1000 weeks 93.63% 35D@5.34% Example 2 145.42 1000 weeks 92.16% 35D@5.98% Example 3 145.72 1000 weeks 93.01% 35D@6.72% Example 4 144.65 1000 weeks 92.86% 35D@6.18% Example 5 143.78 1000 weeks 91.73% 35D@7.21% Example 6 144.67 1000 weeks 92.85% 35D@6.53% Example 7 145.32 1000 weeks 93.01% 35D@6.01% Example 8 145.78 1000 weeks 92.73% 35D@6.75% Example 9 144.58 1000 weeks 90.65% 35D@8.96% Example 10 145.72 1000 weeks 91.02% 35D@7.63% Embodiment 11 144.24 1000 weeks 92.56% 35D@6.93% Example 12 143.65 1000 weeks 93.73% 35D@8.54% Embodiment 13 143.86 1000 weeks 93.86% 35D@7.83% Embodiment 14 143.42 1000 weeks 92.94% 35D@7.35%

[0201] It can be seen from Tables 1 to 3 that the lithium supplement provided by the embodiments of the present invention is applied to a battery in which a lithium iron phosphate positive electrode material is combined with a graphite system negative electrode material, which can improve the battery's charge and discharge specific capacity and cycle retention rate, and can reduce gas production.

[0202] In summary, the lithium supplement provided by the present invention can reduce the ring-opening reaction of ethylene carbonate in the electrolyte, thereby reducing gas production. The preparation method of the lithium supplement is simple, easy to operate, and can be industrially produced. The lithium supplement can be used to prepare batteries, especially for preparing batteries whose negative electrode materials are graphite system materials, which can improve the charge and discharge specific capacity and cycle retention rate of the battery, and can reduce gas production.

[0203] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium supplement, characterized in that: The lithium supplement comprises a core-shell structure, wherein the material forming the core comprises at least one of a lithium ferrite material and a lithium silicate material, and the material forming the shell comprises at least one of a lithium-rich nickel oxide, a nickel-cobalt-manganese ternary material, and a nickel-cobalt binary material; At least a portion of the material forming the outer shell is coated on the surface of the inner core.

2. The lithium supplement according to claim 1, characterized in that: The lithium supplement comprises a lithium ferrite material and a lithium-rich nickel oxide material; The lithium ferrite material forms a core, and at least a portion of the lithium-rich nickel-acid lithium material is coated on the surface of the lithium ferrite material; Preferably, the shell of the lithium supplement comprises a lithium-rich lithium nickelate coating layer coated on the surface of the lithium ferrite material, and a lithium-rich lithium nickelate material free on the surface of the lithium-rich lithium nickelate coating layer or existing alone; Preferably, the surface of the lithium ferrite material has a carbon coating layer, and the lithium-rich lithium nickel oxide coating layer is located on the surface of the carbon coating layer; Preferably, the thickness of the lithium-rich nickelate coating layer is 100 nm to 3 μm.

3. A method for preparing a lithium supplement as claimed in claim 1 or 2, characterized in that: The following steps are involved: The inner core is prepared, and the outer shell is prepared on the surface of the inner core.

4. The preparation method according to claim 3, characterized in that: The lithium supplement comprises a lithium ferrite material and a lithium-rich nickel oxide material; A mixture including a first lithium source and an iron source is pre-sintered and then sintered for the first time to obtain a lithium ferrite material; the lithium ferrite material is mixed with a second lithium source and a nickel source and then sintered for the second time to obtain a lithium ferrite material with a lithium-rich nickel oxide coating layer.

5. The preparation method according to claim 4, characterized in that: The mixture includes at least one of the following characteristics: Feature 1: The molar ratio of Li in the first lithium source to Fe in the iron source is 1.01:1 to 1.50:1; Feature 2: The first lithium source includes at least one of lithium hydroxide, lithium oxide, lithium carbonate and lithium acetate; preferably, the first lithium source includes at least one of lithium oxide and lithium hydroxide; Feature 3: D of the first lithium source 50 10μm~30μm; Feature 4: The iron source includes at least one of Fe2O3, FeCl3 and Fe(NO3)3; preferably, the iron source includes Fe2O3; Feature 5: The mixture also includes a carbon source; preferably, the carbon source includes an organic carbon source; more preferably, the carbon source includes at least one of glucose and acetylene black; preferably, the amount of the carbon source added is 0.5% to 5% of the total mass of the lithium ferrite material.

6. The preparation method according to claim 4 or 5, characterized in that: The pre-sintering temperature is 400°C to 500°C, and the pre-sintering time is 7h to 10h; Preferably, the pre-sintering is performed under an inert atmosphere.

7. The preparation method according to claim 4 or 5, characterized in that: The temperature of the first sintering is 600°C to 900°C; the time of the first sintering is 5h to 15h; Preferably, the first sintering is performed in an inert atmosphere; Preferably, the heating rate of the first sintering is 1° C. / min to 10° C. / min.

8. The preparation method according to claim 4 or 5, characterized in that: The molar ratio of Li in the second lithium source to Ni in the nickel source is 1.1:1 to 1.5:1, and the mass ratio of the nickel source to the lithium ferrite material is 0.01:1 to 5:1; Preferably, the second lithium source includes at least one of lithium hydroxide, lithium oxide, lithium carbonate and lithium acetate; Preferably, the nickel source includes at least one of Ni(OH)2, NiO and NiCO3.

9. The preparation method according to claim 4 or 5, characterized in that: The temperature of the second sintering is 500°C to 800°C; the time of the second sintering is 6h to 15h; Preferably, the second sintering is performed in an inert atmosphere; Preferably, the heating rate of the second sintering is 1°C / min to 10°C / min; Preferably, the lithium ferrite material is first crushed to obtain a first crushed material; the first crushed material is then mixed with the second lithium source and the nickel source and then sintered for a second time; Preferably, the particle size of the first crushed material is in the range of 0.5 μm to 10 μm; Preferably, the second sintered material obtained by the second sintering is crushed for the second time; Preferably, the particle size of the material after the second crushing is in the range of 5 μm to 15 μm.

10. Use of the lithium supplement agent as claimed in claim 1 or 2 in battery preparation; Preferably, the lithium supplement is used for preparing the positive electrode sheet in the battery; Preferably, the lithium supplement agent is used to prepare the positive electrode slurry of the positive electrode plate; Preferably, the positive electrode slurry comprises a lithium iron phosphate positive electrode material, a conductive agent, a binder and the lithium supplement agent; Preferably, the positive electrode slurry comprises 0.5wt% to 5wt% of the lithium supplement agent, 92wt% to 98wt% of the lithium iron phosphate positive electrode material, 0.5wt% to 3wt% of the conductive agent, and the balance is the binder; Preferably, the negative electrode material of the battery is a graphite system material.

Citation Information

Cited By

  • Preparation method of composite lithium supplement additive Li5FeO4-coated Li2NiO2

    CN120817628A